2011
DOI: 10.1111/j.1751-5823.2011.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fundamentalness in Structural Econometric Models: A Review

Abstract: Current economic theory typically assumes that all the macroeconomic variables belonging to a given economy are driven by a small number of structural shocks. As recently argued, apart from negligible cases, the structural shocks can be recovered if the information set contains current and past values of a large, potentially infinite, set of macroeconomic variables. However, the usual practice of estimating small size causal Vector AutoRegressions can be extremely misleading as in many cases such models could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 69 publications
(136 reference statements)
0
53
0
Order By: Relevance
“…n fact, contrary to what is generally assumed in theoretical models, government consumption and invest-5 The issue of non-fundamentalness in VARs was originally studied by Hansen and Sargent (1980), and Reichlin (1993, 1994). A comprehensive review is in Alessi et al (2011).…”
Section: Troubles With Small Fiscal Varsmentioning
confidence: 99%
“…n fact, contrary to what is generally assumed in theoretical models, government consumption and invest-5 The issue of non-fundamentalness in VARs was originally studied by Hansen and Sargent (1980), and Reichlin (1993, 1994). A comprehensive review is in Alessi et al (2011).…”
Section: Troubles With Small Fiscal Varsmentioning
confidence: 99%
“…3 An additional advantage of factor analysis is that the responses to a spending shock do not suffer from foresight issues 4 (see Forni and Gambetti 2010;Forni et al 2009), a problem further alleviated in this paper through the use of a business confidence indicator. Additionally, as Forni et al (2009) and Alessi et al (2011) have shown, the inclusion of more information about the economy through the factors avoids potential VAR non-fundamentalness issues that might arise, such as the ones presented in Lippi and Reichlin (1993).…”
Section: Introductionmentioning
confidence: 99%
“…DSGE, anticipated shocks and nonfundamentalness Yet Lippi and Reichlin (1993) argue that economic models can lead to nonfundamental representations of the data. As surveyed in Alessi et al (2011) and Lütkepohl (2012), nonfundamentalness is basically of two kinds: one which is peculiar to the story-telling of the DSGE and the other which arises as an omitted variable problem. In the former case, nonfundamentalness is model-based and the economic shocks may well be nonfundamental with respect to any set of observables (models with imperfect information where the agents are faced with a ltering problem to infer the structural shocks).…”
Section: Proof In Appendixmentioning
confidence: 99%